To solve the system of equations:
- \( 3x + 4y = 48 \) (Equation 1)
- \( 6x + 2y = 60 \) (Equation 2)
Step 1: Choose the best method
A good method to solve this system is the elimination method. We can manipulate the equations to get the \( x \) variables to cancel each other out.
Step 2: Get the \( x \) variables to cancel out
To do this, we can multiply Equation 1 by 2 so that the coefficients of \( x \) will match:
\[ 2(3x + 4y) = 2(48) \] This simplifies to:
\[ 6x + 8y = 96 \quad \text{(New Equation 1)} \]
Now we have:
- \( 6x + 8y = 96 \) (New Equation 1)
- \( 6x + 2y = 60 \) (Equation 2)
Step 3: Line them up and subtract
Next, we subtract Equation 2 from the New Equation 1 to eliminate \( x \):
\[ (6x + 8y) - (6x + 2y) = 96 - 60 \]
This simplifies to:
\[ (8y - 2y) = 36 \] \[ 6y = 36 \]
Step 4: Solve for \( y \)
Now, solve for \( y \):
\[ y = \frac{36}{6} = 6 \]
Step 5: Solve for \( x \)
Now that we have \( y \), we can substitute \( y = 6 \) back into either original equation to solve for \( x \). We'll use Equation 1:
\[ 3x + 4(6) = 48 \] \[ 3x + 24 = 48 \] Subtract 24 from both sides:
\[ 3x = 48 - 24 \] \[ 3x = 24 \]
Divide by 3:
\[ x = \frac{24}{3} = 8 \]
Final solution
The solution to the system of equations is:
- \( x = 8 \)
- \( y = 6 \)